The impact of indoor air quality on respiratory health of older people living in nursing homes: spirometric and exhaled breath condensate assessments - Belo, Joana (2020)
In the Portuguese Geriatric Study of the Health Effects of Indoor Air Quality in Senior Nursing Homes, we aimed to evaluate the impact of indoor air contaminants on the respiratory symptoms and biomarkers in a sample of elderly living in nursing homes. A total of 269 elderly answered a health questionnaire, performed a spirometry and 150 out of these collected an exhaled breath condensate sample for pH and nitrites analysis. The study included the evaluation of indoor chemical and microbiological contaminants. The median age of the participants was 84 (78-87) years and 70.6% were women. The spirometric data indicated the presence of airway obstruction in 14.5% of the sample. Median concentrations of air pollutants did not exceed the existing standards, although increased peak values were observed. In the multivariable analysis, each increment of 100 µg/m3 of total volatile organic compounds was associated with the odds of respiratory infection in the previous three months ( OR̂ =1.05; 95% CI: 1.00-1.09). PM2.5 concentrations were inversely associated with pH values ( β̂ = -0.04, 95%: -0.06 to -0.01, for each increment of 10 µg/m3). Additionally, a direct and an inverse association were found between total bacteria and FEV1/FVC and FVC, respectively.